THE APPLICATION OF EARNED VALUE MANAGEMENT (EVM) IN CONSTRUCTION PROJECT MANAGEMENT - Chin Keng, Tan; Shahdan, Najihah (Journal of Technology Management and Business, 2015)
Earned Value Management (EVM) is a methodology that combines scope, schedule, and resource measurements to assess project performance and progress, it involves the integration of the three key elements of project which are schedule, work scope, and cost. Based on the literatures, various benefits have been associated with the use of EVM in project management. The objectives of this study are to determine the level of awareness on EVM among construction practitioners in Malaysia and to investigate whether EVM is been applied in Malaysia construction projects. For the purpose of data collection, this research applied questionnaire survey technique. This findings of this study reveal that key players in construction industry have very low level of awareness on EVM. The study identified that the key players in Malaysia construction industry have applied some parts of EVM concepts during construction projects but the application is not found to be intensive. It is recommended that much efforts to be made in order to enhance the awareness and increase the level of application on EVM among the key players in the construction industry.